2020
DOI: 10.21203/rs.3.rs-50212/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Knowledge and Practice to Prevent Against Corona Virus Disease (COVID-19) and Its Associated Factors Among Pregnant Women in Debre Tabor Town Northwest Ethiopia: a Community Based Cross-Sectional Study.

Abstract: Background: The current corona virus disease (COVID-19) is now become the global concerns and declared as a pandemic by World Health Organization on March 2020. To date, no antiviral treatment or vaccine has been explicitly recommended for COVID-19. So, applying preventive measures to control COVID-19 infection is the most critical intervention. Pregnant women are particularly susceptible to respiratory pathogens and severe pneumonia, because they are at immunosuppressive state and physiological adaptive chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 14 publications
(26 reference statements)
5
13
0
Order By: Relevance
“…In another way younger participants have a better educational level, and another study has shown participants with a higher level of education have better preventive practices. 38 Results of this study also showthat younger participants have a better educational status when compared to older participants.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…In another way younger participants have a better educational level, and another study has shown participants with a higher level of education have better preventive practices. 38 Results of this study also showthat younger participants have a better educational status when compared to older participants.…”
Section: Discussionsupporting
confidence: 53%
“…Consistently, a study conducted in Debre Tabor town shows that participants aged 15–24 were more likely to practice COVID-19 preventive measures. 38 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…25 However, the trend of confirmed COVID-19 cases in Ethiopia has shown that it is better than the US and European countries, though they had comparatively higher testing capacities. Having significant level of inadequate preventive practice measures in Ethiopia, 26,27 thus there is important to comprehend the trend of COVID-19 and to generalize the implications of the strategies used by the government to mitigate the spread of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…AI may also help to decide which patients should be prioritized for treatment and quickly learn which factors predict a higher risk of mortality, as well interventions and population-level controls, have led to reduced harm. 33,34 As the number of COVID-19 cases increased nationally in Ethiopia and different studies showed the majority of the community had poor practice on preventive measures, 26,27 there should be a need to focus on further measures to minimize the spread of COVID-19.…”
Section: Dovepressmentioning
confidence: 99%